WUS-FRESH (Wanita Usia Subur – Fluor Albus Education For Reproductive Health): Penyuluhan untuk Meningkatkan Pengetahuan Tentang Fluor Albus - Anak Agung Sagung Ratu Putri Saraswati; Ni Made Padma Batiari; Kadek Sri Ariyanti; I Desak Ketut Dewi Satiawati Kurnianingsih; Luh Verra Sridyantari (UNIVERSITAS NGUDI WALUYO, 2026)
Women of Childbearing Age (WUS) are a group of women aged 15–49 years who are in their active reproductive phase and are at high risk of reproductive health problems. One common problem is vaginal discharge (fluor albus). Lack of knowledge about the characteristics of normal and abnormal vaginal discharge causes many women to ignore symptoms that can indicate reproductive tract infections, sexually transmitted diseases, and even complications that can affect fertility. To increase knowledge of women of childbearing age about vaginal discharge through reproductive health education activities. The activity was carried out in several stages, including: 1) Preparation; 2) Pre-test data collection; 3) Implementation of counseling using lecture and discussion methods using flyer media; 4) Post-test data collection (evaluation). Pre-test and post-test data collection was carried out qualitatively by means of interviews regarding the material provided. The target of the activity was women of childbearing age (WUS) in Br. Batur Sari, Kesiman Kertalangu Village, Denpasar. There was an increase in WUS knowledge about fluor albus after being given education. The WUS-FRESH program not only contributes to increasing knowledge about fluor albus, but also supports promotive and preventive efforts for reproductive health. Sustainability of the program is highly recommended by involving health workers and community cadres, so that its positive impact can reach more WUS and contribute to improving the quality of reproductive health in a sustainable manner. ABSTRAK Wanita Usia Subur (WUS) merupakan kelompok perempuan berusia 15–49 tahun yang berada pada fase aktif reproduksi dan memiliki risiko tinggi terhadap masalah kesehatan reproduksi. Salah satu permasalahan yang sering terjadi adalah fluor albus (keputihan). Kurangnya pengetahuan tentang karakteristik keputihan normal dan abnormal menyebabkan banyak wanita mengabaikan gejala yang dapat mengarah pada infeksi saluran reproduksi, penyakit menular seksual, bahkan komplikasi yang dapat memengaruhi kesuburan. Meningkatkan pengetahuan wanita usia subur mengenai fluor albus melalui kegiatan penyuluhan kesehatan reproduksi. Kegiatan dilakukan dalam ebebrapa tahapan, antara lain: 1) Persiapan; 2) Pengambilan data pre-test; 3) Pelaksanaan penyuluhan dengan metode ceramah dan diskusi menggunakan media flyer; 4) Pengambilan data post-test (evaluasi). Pengambilan data pre-test dan post-test dilakukan secara kualitatif dengan cara wawancara seputar materi yang diberikan. Sasaran kegiatan adalah wanita usia subur (WUS) di Br. Batur Sari Desa Kesiman Kertalangu, Denpasar. Terdapat peningkatan pengetahuan WUS tentang fluor albussetelah diberikan edukasi. Program WUS-FRESH tidak hanya berkontribusi pada peningkatan pengetahuan tentang fluor albus, tetapi juga mendukung upaya promotif dan preventif kesehatan reproduksi. Keberlanjutan program sangat disarankan dengan melibatkan tenaga kesehatan dan kader masyarakat, agar dampak positifnya dapat menjangkau lebih banyak WUS dan berkontribusi pada peningkatan kualitas kesehatan reproduksi secara berkelanjutan.